2012
DOI: 10.3390/toxins4100849
|View full text |Cite
|
Sign up to set email alerts
|

Do Only Small Uremic Toxins, Chromophores, Contribute to the Online Dialysis Dose Monitoring by UV Absorbance?

Abstract: The aim of this work was to evaluate the contributions of the main chromophores to the total UV absorbance of the spent dialysate and to assess removal dynamics of these solutes during optical on-line dialysis dose monitoring. High performance chromatography was used to separate and quantify UV-absorbing solutes in the spent dialysate sampled at the start and at the end of dialysis sessions. Chromatograms were monitored at 210, 254 and 280 nm routinely and full absorption spectra were registered between 200 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…3 ). This has been confirmed also by earlier studies [11,12] . Moreover, HPLC studies have demonstrated that UA is an UV-absorbing solute in the studied wavelength range, and therefore influences the UV-signal substantially [13] .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…3 ). This has been confirmed also by earlier studies [11,12] . Moreover, HPLC studies have demonstrated that UA is an UV-absorbing solute in the studied wavelength range, and therefore influences the UV-signal substantially [13] .…”
Section: Discussionsupporting
confidence: 81%
“…For the determination of UV-absorbance (A) in the spent dialysate/ultrafiltrate, described earlier [9][10][11] , a double-beam spectrophotometer (V-570, UV/VIS/NIR spectrophotometer and software version 1.53.01 for Windows, JASCO Corp., Japan) with an accuracy of ±0.3% was used. Scanning at the UV-range 190-400 nm was performed after each session using pure dialysate as reference.…”
Section: Uv-absorbance Scanningmentioning
confidence: 99%
“…Along these lines, several non-uremic solutes, drug metabolites and unidentified molecules that contribute significantly to the UV absorbance signal during dialysis have been found by chromatography in the spent dialysate [11]. One such molecule is uric acid, which has been identified as a major contributor to total dialysate UV absorbance [11]. Interestingly, Kanbay et al [12] found a correlation between dietary fructose intake and elevated uric acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, other rapidly absorbed molecules could account for the changes. Along these lines, several non-uremic solutes, drug metabolites and unidentified molecules that contribute significantly to the UV absorbance signal during dialysis have been found by chromatography in the spent dialysate [11]. One such molecule is uric acid, which has been identified as a major contributor to total dialysate UV absorbance [11].…”
Section: Discussionmentioning
confidence: 99%
“…The peak of UA is well separated from peaks of PAR and its metabolites on the chromatograms [12] and any possibility of analytical interference of PAR+ metabolites in HPLC estimation of UA content in spent dialysate seems not to be possible. Consequently, the significant rise of content of UA in spent dialysate after dosage of PAR to ESRD patients in the course of dialysis session seems to really take place at least in some cases of treatments.…”
Section: Discussionmentioning
confidence: 99%